Proinflammatory allogeneic dendritic cells enhance the therapeutic efficacy of systemic anti-4-1BB treatment - Ali, Arwa; Gao, Menghan; Iskantar, Alexandros; Wang, Hai; Karlsson-Parra, Alex; Yu, Di; Jin, Chuan (Frontiers in Immunology, 2023)
As an immune adjuvant, proinflammatory allogeneic dendritic cells (AlloDCs) have demonstrated promising immune-priming effects in several preclinical and clinical studies. The effector cells, including NK cells and T cells are widely acknowledged as pivotal factors in the effectiveness of cancer immunotherapy due to their ability to selectively identify and eradicate malignant cells. 4-1BB, as a costimulatory receptor, plays a significant role in the stimulation of effector cell activation. This study evaluated the anti-tumor effects when combining intratumoral administration of the immune-adjuvant AlloDCs with systemic α4-1BB treatment directly acting on effector cells.In both the CT-26 murine colon carcinoma model and B16 murine melanoma model, AlloDCs demonstrated a significant enhancement in the therapeutic efficacy of α4-1BB antibody. This enhancement was observed through the delayed growth of tumors and prolonged survival. Analysis of the tumor microenvironment (TME) in the combined-treatment group revealed an immuneinflamed TME characterized by increased infiltration of activated endogenous DCs and IFNγ + CD8 + T cells, showing reduced signs of exhaustion. Furthermore, there was an augmented presence of tissue-resident memory (TRM) CD8 + T cells (CD103 + CD49a + CD69 + ). The combination treatment also led to increased infiltration of CD39 + CD103 + tumor-specific CD8 + T cells and neoantigen-specific T cells into the tumor. Additionally, the combined treatment resulted in a less immunosuppressive TME, indicated by decreased infiltration of myeloid-derived suppressor cells and Tregs. These findings suggest that the combination of intratumoral AlloDCs administration with systemic agonistic α4-1BB treatment can generate a synergistic anti-tumor response, thereby warranting further investigation through clinical studies.